Designing ZrO2-based catalysts for the direct synthesis of isobutene from syngas: The studies on Zn promoter role. (1st May 2019) - Wu, Xuemei; Tan, Minghui; Tian, Sha; Song, Faen; Ma, Qingxiang; He, Yingluo; Yang, Guohui; Tsubaki, Noritatsu; Tan, Yisheng
Graphical abstract: Highlights: Trace Zn dopant could obviously influence the selective synthesis of isobutene. Formate species were more favorable for the synthesis of isobutene. Appropriate amount of Zn dopant could stabilize the formate species. Abstract: Selective synthesis of isobutene from syngas is a promising route, but still in a great challenge, to realize the isobutene production from non-petroleum carbon resources. In this work, aiming at realizing more efficient isobutene synthesis from syngas, a series of ZrO2 -based catalysts with varied amount of Zn dopant as promoter, were prepared and studied. The catalytic performance of pure ZrO2 and new Znx Zry Oz catalysts with Zn/Zr of different molar ratio was evaluated, and the Zn1 Zr300 Oz catalyst exhibited promoted isobutene selectivity, better than other catalysts. In order to disclose the promotional role of Zn dopant to the enhanced catalyst performance, XRD, TEM, NH3 /CO2 -TPD and in-situ FTIR techniques were employed. The characterization results revealed that trace amount of Zn dopant could affect the acidic-basic properties and the adsorbed species of the Znx Zry Oz catalysts. The CO2 -TPD analysis proved that the incorporation of Zn could clearly enhance the surface basicity of Znx Zry Oz catalysts. The in-situ FTIR analysis uncovered that the peak intensity of formate and carbonate species on the surface of Znx Zry Oz catalysts was different. The optimal Zn1 Zr300 Oz catalyst displayed more moderate basic sites and less strong acidic sites. It also exhibited the strongest intensity of formate species and the weakest intensity of carbonate species. These specific features of Zn1 Zr300 Oz catalyst should be beneficial to the synthesis of isobutene from syngas.